The Cardiovascular and Metabolic Effects of Chronic Hypoxia in Animal Models: A Mini-Review - Barnes, Laura A.; Mesarwi, Omar A.; Sanchez-Azofra, Ana (Frontiers in Physiology, 2022)
Animal models are useful to understand the myriad physiological effects of hypoxia. Such models attempt to recapitulate the hypoxemia of human disease in various ways. In this mini-review, we consider the various animal models which have been deployed to understand the effects of chronic hypoxia on pulmonary and systemic blood pressure, glucose and lipid metabolism, atherosclerosis, and stroke. Chronic sustained hypoxia (CSH)—a model of chronic lung or heart diseases in which hypoxemia may be longstanding and persistent, or of high altitude, in which effective atmospheric oxygen concentration is low—reliably induces pulmonary hypertension in rodents, and appears to have protective effects on glucose metabolism. Chronic intermittent hypoxia (CIH) has long been used as a model of obstructive sleep apnea (OSA), in which recurrent airway occlusion results in intermittent reductions in oxyhemoglobin saturations throughout the night. CIH was first shown to increase systemic blood pressure, but has also been associated with other maladaptive physiological changes, including glucose dysregulation, atherosclerosis, progression of nonalcoholic fatty liver disease, and endothelial dysfunction. However, models of CIH have generally been implemented so as to mimic severe human OSA, with comparatively less focus on milder hypoxic regimens. Here we discuss CSH and CIH conceptually, the effects of these stimuli, and limitations of the available data.